INVESTOR OR INTRUDER, LAW ENFORCEMENT ON FOREIGN STAY PERMIT VIOLATIONS IN INDONESIA - Putra, Komang Satria Wibawa; Prasada, Dewa Krisna; Astawa, I Nengah Dasi (EKSEKUSI, 2025)
The purpose of this study is to analyze various regulations of foreign citizens in obtaining limited stay permits and law enforcement on the abuse of limited stay permits by foreign investors in Indonesia. The type of research in this writing is doctrinal research with a legislative and conceptual approach that focuses on laws and regulations and literature as sources of legal material. After the legal materials are collected by conducting literature research, the next step is to analyze descriptively and argumentatively. Based on the results of the study, it shows that the procedure for owning an investor KITAS in Indonesia has provided legal certainty and made it easier for foreign citizens to invest in Indonesia as one of the main factors that attract investors to invest. Foreign nationals who will invest must meet several document requirements and establish a PT PMA with capital provisions in accordance with applicable regulations. Administrative action against the misuse of investor KITAS by foreign nationals is carried out by Immigration Officials as a form of law enforcement which is an attributive authority granted by law. The administrative action that can be taken by Immigration Officials for the misuse of investor KITAS is deportation from Indonesian territory. The synergy of the three main components in the legal system can create consistent, optimal, and effective law enforcement against the abuse of investors' KITASKeywords: foreign investors, limited stay permits, law enforcement, immigration policies, legal compliance